Cloud outsourcing secret sharing scheme against covert adversaries - En ZHANG; Kui GENG; Wei JIN; Yong-jun LI; Yun-qing SUN; Feng-hua LI (Tongxin xuebao)
In order to make computationally weak cloud tenants can reconstruct a secret with efficiency and fairness,a cloud outsourcing secret sharing scheme was proposed,which combined cloud outsourcing computation with secret sharing scheme.In the process of outsourcing secret sharing,cloud tenants just need a small amount of decryption and validation operations,while outsource expensive cryptographic operations to cloud service provider (CSP).The scheme,without complex interactive augment or zero-knowledge proof,could detect malicious behaviors of cloud tenants or cloud service providers.And the scheme was secure against covert adversaries.Finally,every cloud tenant was able to obtain the secret fairly and correctly.Security analysis and performance comparison show that scheme is safe and effective.